Um framework para criação de ambientes colaborativos - Natalli, Eleu Lima (2011)
The Web offers an unprecedented opportunity to promote the integration of persons to perform activities of any nature, whether for work, for leisure or for study. With this one sees growing demand for new collaborative applications. In this context we have seen an emerging class of applications called Collaborative Environments. Although much progress has been made with the emergence of general-purpose environments, where VLEs and CMSs stand out, it has been observed that these do not always fit the needs and preferences of specific groups. It is therefore desirable to offer facilitators for creating innovative proposals. In this work, we present a framework for the development of environments of this class of applications. The aim of the proposal is to facilitate the process of building this kind of environments, promoting artifacts facilitators to use, according to the approach of the 3C collaboration model. The proposal was built on the methodology Hot-Spot-Driven Design coupled with best practices of software engineering, in addition to using the concepts of Intellectual Production Unit (UPI) and communication vehicle (Vcom) for modeling collaborative spaces proposed in the MOrFEu project. Finally, the work also presents a prototype of the proposed framework as a way of materializing the concepts described and enhance the viability of the proposal, creating a set of collaborative environments.